Business process redesign project success: the role of socio-technical theory. Issue 5 (26th August 2014) - Xiang, Junlian; Archer, Norm; Detlor, Brian
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to seek to advance business process redesign (BPR) project research through the generation and testing of a new research model that utilizes formative constructs to model complex BPR project implementation issues. Instead of looking at management principles, the paper examines the activities of improving business processes from the project perspective. Design/methodology/approach – A survey of 145 managers and executives from medium and large-sized USA and Canadian companies was used to validate the model. Findings – The model, based on socio-technical theory, includes three implementation components (change management, process redesign, and information and communication technology infrastructure improvement), and links the effects of these components to BPR project outcomes. The empirical findings indicated that all three implementation components had a significant impact on BPR project success, with change management having the greatest effect. Interestingly, the results also showed that productivity improvement was no longer the main focus of companies carrying out BPR projects; instead, improvement in operational and organizational quality was more important. Research limitations/implications – The main limitation of this study is its generalizability with respect to company size and organizational culture. The sample in this study was drawn from medium- and large-sized companies in Canada and the USA, but small-sized organizations were excluded from this study due to their distinct features (e.g. superior flexibility or ability to reorient themselves quickly). Also, this study controlled the variable of organizational culture by limiting respondents to Canada and US companies. It would be very interesting to investigate BPR project implementations in other countries where the organizational working culture may be different. Practical implications – Based on the findings of this study, BPR practitioners can refer to the three BPR project implementation components and then prioritize and sequence the tasks in a BPR project to achieve their preset BPR goals. Originality/value – This is the first study which utilizes formative constructs to validate the important BPR project components.